ANALISIS JUMLAH KEBUTUHAN DOKTER UMUM DENGAN METODE WISN (WORKLOAD INDICATORS STAFFING NEED) DI POLI UMUM UPTD PUSKESMAS MUSTIKA JAYA KOTA BEKASI TAHUN 2020 - Martha Lidya Roberta Sihombing (2021)
Human resource planning is an activity of estimate staffing need of an organization so the type and quantitiy can be determined according to the needs. One of methods in planning health workers needs is the Workload Indicators Staffing Need (WISN) method. This study aims to analyze the optimal number of general doctors by using the Workload Indicators of Staffing Need through observation using work sampling technique at General Poly of the Primary Health Care Mustika Jaya of Bekasi City in 2020. Work sampling was done every five minute in six work days. This study uses a qualitative type of research with descriptive design. The result of this study indicate that the working time for general doctors are 78.180 minutes/year. Then, the workload standar of the general doctors were 20.848 for medical services, 15.636 for follow-up services, and 26.051,31 for referral-making services. The supporting task standard was 1,96. The results of WISN calculations obtained were by the shortage of one doctor. Improved service quality is needed by adding workforce and evaluating.